Immunoproteasome modulates NLRP3 inflammasome‐mediated neuroinflammation under cerebral ischaemia and reperfusion conditions. Issue 2 (6th December 2021) - Chen, Xingyong; Wang, Yinzhou; Yao, Nannan; Lin, Zejing
Abstract: Compelling evidence showed that both nucleotide‐binding oligomerization domain‐like receptor family, pyrin domain‐containing protein 3 (NLRP3) inflammasomes and the immunoproteasome participate in neuroinflammatory responses in cerebral ischaemia injury. Moreover, inhibition of either NLRP3 inflammasomes or the immunoproteasome attenuates both neuroinflammation and neurological deterioration during ischaemic stroke. However, the underlying mechanism between the immunoproteasome and NLRP3 inflammasomes under ischaemic stroke conditions remains to be established. In this study, using both in vitro and in vivo ischaemic models, we demonstrated that the immunoproteasome inhibition reduced the expressions of NLRP3 inflammasome‐associated proteins, including NLRP3, apoptosis‐associated speck‐like protein (ASC), caspase‐1 and mature cytokines (interleukin [IL]‐1β and IL‐18). It also downregulated the levels of nuclear factor (NF)‐κB and pyroptotic‐ and apoptotic‐related proteins, and improved cell viability. In addition, inhibition of NF‐κB by the small molecule inhibitor Bay‐11‐7082 led to lower levels of NLRP3 inflammasomes and cleaved caspase‐1 proteins in BV2 cells after oxygen‐glucose deprivation and reoxygenation. Together, these findings suggest that the immunoproteasome may be responsible for inducing the expression and activation of NLRP3 inflammasomes via the NF‐κB pathway. Therapeutic interventions that target activation of the immunoproteasome/NF‐κB/NLRP3 inflammasome pathway may provide novel prospects for the future treatment of ischaemic stroke.